Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1161/circulationaha.106.665406
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Type-1 Long-QT Syndrome by Location, Coding Type, and Biophysical Function of Mutations Involving the KCNQ1 Gene

Abstract: Background-Type-1 long-QT syndrome (LQTS) is caused by loss-of-function mutations in the KCNQ1-encoded I Ks cardiac potassium channel. We evaluated the effect of location, coding type, and biophysical function of KCNQ1 mutations on the clinical phenotype of this disorder. Methods and Results-We investigated the clinical course in 600 patients with 77 different KCNQ1 mutations in 101 proband-identified families derived from the US portion of the International LQTS Registry (nϭ425), the Netherlands' LQTS Registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
289
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 399 publications
(306 citation statements)
references
References 29 publications
(22 reference statements)
13
289
4
Order By: Relevance
“…Conversely, we found a maternal transmission rate of 67% for the dominant negative variants, which are associated with the most severe channel dysfunction, compared with 58% for non-dominant negative variants. 8 Thus, the degree of transmission distortion in LQTS may vary among populations depending on variant type. This may explain the absence of significant female predominance/transmission distortion recently reported in a Norwegian population where most of the identified LQT1 variants led to haploinsufficiency and a moderate channel dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, we found a maternal transmission rate of 67% for the dominant negative variants, which are associated with the most severe channel dysfunction, compared with 58% for non-dominant negative variants. 8 Thus, the degree of transmission distortion in LQTS may vary among populations depending on variant type. This may explain the absence of significant female predominance/transmission distortion recently reported in a Norwegian population where most of the identified LQT1 variants led to haploinsufficiency and a moderate channel dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, KCNQ1 co-assembles with KCNE1, the major cardiac β-subunit, to form the slowly activating K+ channel sensitive to adrenergic regulation. 8,26 In contrast, co-assembly of KCNQ1 with KCNE3 produces a current with nearly instantaneous activation. 27 In colonic crypts, these KCNQ1:KCNE3 channels mediate basolateral K + recycling required for Cl − secretion and their expression is regulated by estrogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In a recent study on 356 LQT1 mutation carriers with known or suspected alterations in the ion-channel function, it was demonstrated that the degree of channel dysfunction in vitro was a major risk factor for cardiac events, independent of clinical risk factors and ␤-blocker therapy. 11 However, it has been recently proposed that cellular electrophysiological studies cannot always predict the clinical phenotype of a mutation; despite the severe clinical pheno- type of the A341V mutation carriers, only a mild dominant negative effect was demonstrated in vitro. 7,8 It is evident that clinical observations should modulate the interpretation of experimental findings.…”
Section: Functional Studies and Clinical Severitymentioning
confidence: 99%
“…High-risk mutations have been identified within the LQT1 subgroup. [7][8][9][10][11] The Y111C-KCNQ1 (c.332AϾG) mutation has previously been described in 1 patient, a 36-year-old woman, who presented with syncope at the age of 3 years. 3 She experienced Ͼ30 syncopal episodes triggered by emotional or physical stress and had a QT interval, corrected for heart rate, of 520 ms. Electrophysiological studies subsequently demonstrated that the Y111C mutation causes intracellular sequestration of mutated ion channels in the endoplasmic reticulum that renders them inactive.…”
mentioning
confidence: 99%